ANALYSIS OF RISK FACTORS FOR DEVELOPMENT OF CARDIOVASCULAR DISEASES OF MEN GOER OF BEIRA MAR AVENUE OF FORTALEZA (Fiep Bulletin - online, 2011)
The objective of this study was to analyze the risk factors for cardiovascular disease (CVD) of men who frequent the sidewalk of Beira Mar Avenue in Fortaleza. The sample consisted of 144 men aged 16 to 82 years. The instrument used was a structured interview and measures of body mass (BM), height and waist circumference (WC). The data were analyzed using descriptive statistics (mean, standard deviation and frequency percentage). The results showed a mean age of 44.19 + 16.19 years, height (170.08 + 7.17 cm), BM (74.38 + 11.81 kg), BMI (25.73 + 3.89 ). Risk factors for cardiovascular diseases were WC> 94 cm (33.6%), WC> 102 (13.9%), BMI> 25 kg / m² (54.6%), high total cholesterol (38%), family history of coronary heart disease (39.9%), hypertension (38%) and physical inactivity (36.8%). It is concluded that frequent the sidewalk are at risk of CVD and require the practice of regular physical activity, preferably at least three times a week with low to moderate intensity (55-90% HRmáx) at least thirty minutes and change eating habits.
Keywords: cardiovascular disease; exercise; risk factors